Adenosine A2A receptors format long-term depression and memory strategies in a mouse model of Angelman syndrome - Moreira-de-Sá, Ana (2020)
Angelman syndrome (AS) is a neurodevelopmental disorder caused by loss of function of the maternally inherited Ube3a neuronal protein, whose main features comprise severe intellectual disabilities and motor impairments. Previous studies with the Ube3am-/p+ mouse model of AS revealed deficits in synaptic plasticity and memory. Since adenosine A2A receptors (A2AR) are powerful modulators of aberrant synaptic plasticity and A2AR blockade prevents memory dysfunction in various brain diseases, we tested if A2AR could control deficits of memory and hippocampal synaptic plasticity in AS. We observed that Ube3am-/p+ mice were unable to resort to hippocampal-dependent search strategies when tested for learning and memory in the Morris water maze; this was associated with a decreased magnitude of long-term depression (LTD) in CA1 hippocampal circuits. There was an increased density of A2AR in the hippocampus of Ube3am-/p+ mice and their chronic treatment with the selective A2AR antagonist SCH58261 (0.1 mg/kg/day, ip) restored both hippocampal-dependent learning strategies, as well as LTD deficits. Altogether, this study provides the first evidence of a role of A2AR as a new prospective therapeutic target to manage learning deficits in AS.